Spatialities of entrepreneurial ecosystems - Schäfer, Susann (Geography compass, 2021)
The concept of entrepreneurial ecosystems has gained tremendous attention in academia across different scientific disciplines. This start-of-the-art contribution addresses the most recent lineages of the entrepreneurial ecosystem debate from a spatial perspective: measurement of entrepreneurial ecosystems, entrepreneurial evolution, novel actors, institutions and events, governance as well as gender in entrepreneurial ecosystems. The theoretical advancements will be critically reviewed by examining the implicit and explicit spatial references. The paper also highlights the potential of using spatial analysis for entrepreneurial ecosystems, drawing on four different understandings of space.